(untitled) (Research, Society and Development, 2021)
Considering that exposure to unpleasant pictures taken from the International Affective Pictures System (IAPS) has a more significant impact on anxiety than exposure to pleasant and neutral pictures, we investigated changes in state anxiety levels and heart rate responses in healthy women following exposure to three blocks of unpleasant pictures from the IAPS. Thirty-seven healthy women visited the lab three times, separated by a gap of 24–72 hours. Anxiety levels were assessed using the State Anxiety Inventory before and after participants viewed the blocks of unpleasant IAPS pictures, while the heart rate was continuously monitored throughout each session by a heart rate monitor. We found extreme evidence (BF10 = 7.53*108) for the changes in the participants’ state anxiety after viewing IAPS unpleasant pictures, although there was ambiguous evidence (BF01 = 2.642) favoring similar changes in state anxiety and ratings of pleasure (BF01 = 1.567), arousal (BF01 = 2.609), and dominance (BF01 = 1.954) between the three blocks of unpleasant pictures used. Moreover, we found moderate evidence (BF01 = 7.449) favoring similar mean heart rates between the three blocks of unpleasant pictures. These findings reveal that exposure to unpleasant pictures can act as an anxiogenic stimulus used to induce experimental anxiety.